Pendampingan Manajemen, dan Inovasi Produk Olahan Dalam Peningkatan Kapasitas Produksi Ternak pada UMKM Ternak Entok Barokah di Desa Gerimax Indah Kecamatan Narmada Kabupaten Lombok Barat - Indah Ariffianti; Erviva Fariantin; Ulfiyani Asdiansyuri; Hikmah; Sukma Hidayat Kurnia A; M. Rido Sa’ban; Siti Aisyah (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi AMM, 2026)
The Community Service Activity with the topic of Management Assistance and Processed Product Innovation in Increasing the Production Capacity of Mr Ahmad’s Muscovy Duck Farm in Gerimax Indah Village, Narmada District, West Lombok Regency, was carried out by lecturers of STIE AMM Mataram together with students. Entok Barokah MSME, which served as the community service partner, is an MSME owned by Mr Ahmad that has been operating for more than five years. So far, Entok Barokah MSME has not had simple financial reports, product variation potential, marketing and branding strategies, or a clearly defined business location. Due to these limitations, it was necessary to provide knowledge and understanding regarding formal marketing and branding as an initial step toward the sustainability and future success of the business, enabling it to compete with other business actors through discussions and mentoring. The results of the community service activity showed that Mr. Ahmad, the owner of Entok Barokah MSME, now has a strong understanding of the importance of: 1) Preparing simple financial reports; 2) Developing processed product innovations in the form of shredded muscovy duck (duck floss); 3) Improving MSME understanding of utilizing digital technology for online marketing and branding activities, particularly through Instagram; and 4) Having an accurate and clearly identifiable business location through Google Maps.